Enhancing Transparency to Mitigate Information Asymmetry: A Study of LQ 45 Companies - Puspita Wulandari, Juniarti; Siagian, Arifin; ‎ , Noviarti (KnE Social Sciences, 2024)
Transparency is essential in information asymmetry as it enables involved parties to make more informed and fair decisions, reducing the risks of inequality and conflicts arising from information ambiguity. With transparency, a conducive environment is created where all parties have equal access to relevant information, supporting integrity and enhancing efficiency in decision-making processes. This study aims to determine the effect of liquidity, and solvency on information asymmetry in LQ 45 companies in 2021 during the Covid-19 pandemic. This study employs a quantitative methodology and is classified as correlational in nature. Secondary data were utilized in this research, which were obtained through observation and documentation from the idx.co.id website and the official website of the organization, which is located at LQ45 2021. Concurrently, employ a linear regression analysis technique to judge the relationship between variables twice. With values of -8561, the results of this study indicate that liquidity has a marginally significant negative impact on information asymmetry. This indicates that tcount>ttable with an important value of 0.001, is < 0.05. However, information asymmetries are not significantly impacted negatively by the solvency ratio. Furthermore, these results demonstrate that alongside solvency and liquidity, one can reduce the information asymmetry that stakeholders acquire. Keywords: asymmetry information, liquidity, solvency, LQ45